2013
DOI: 10.3389/fnhum.2013.00647
|View full text |Cite
|
Sign up to set email alerts
|

What about the “Self” is Processed in the Posterior Cingulate Cortex?

Abstract: In the past decade, neuroimaging research has begun to identify key brain regions involved in self-referential processing, most consistently midline structures such as the posterior cingulate cortex (PCC). The majority of studies have employed cognitive tasks such as judgment about trait adjectives or mind wandering, that have been associated with increased PCC activity. Conversely, tasks that share an element of present-centered attention (being “on task”), ranging from working memory to meditation, have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
194
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(209 citation statements)
references
References 54 publications
10
194
0
5
Order By: Relevance
“…The deactivation of this important hub of the DMN has been related to effortless awareness (Garrison et al 2013a) and was also found deactivated in an fMRI study during focused attention meditation (Garrison et al 2013b). PCC deactivation reportedly reflects increased present-centered awareness, whereas PCC activation is related to being caught up in mental content and is associated with decreased attention (Brewer et al 2013). …”
Section: Discussionmentioning
confidence: 95%
“…The deactivation of this important hub of the DMN has been related to effortless awareness (Garrison et al 2013a) and was also found deactivated in an fMRI study during focused attention meditation (Garrison et al 2013b). PCC deactivation reportedly reflects increased present-centered awareness, whereas PCC activation is related to being caught up in mental content and is associated with decreased attention (Brewer et al 2013). …”
Section: Discussionmentioning
confidence: 95%
“…First, a direct test of the impact of this pattern of altered DMN connectivity on self-referential cognitive processes was outside the scope of the current study. Nevertheless, there is a wealth of evidence suggesting that synchronization between the PCC and aMPFC occurs during tasks involving self-referential thought 73,74 . Second, following Andrews-Hanna et al 11 , we placed seeds only in the left hemisphere of the brain.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…6 Apart from the above-mentioned cluster in the lingual gyrus, we also found another region, the precuneus, in which HC showed a higher response to faces as compared to SAD. Precuneus activity seems to be related to the sense of self 82 and the self-attribution of emotions, as compared to when emotions are attributed to others. 83 Moreover, abnormal activity and connectivity in precuneus has been reported in anxiety disorders, including SAD.…”
mentioning
confidence: 99%